EXPERIENCES CONSTRUCTED IN THE PROCESS OF LIVING WITH A VENOUS ULCER - Dalva Cezar da Silva; Maria de Lourdes Denardin Budó; Maria Denise Schimith; Liliane Ecco; Isabelle Katherinne Fernandes Costa; Gilson de Vasconcelos Torres (Universidade Federal do Paraná, 2015)
The aim of this study was to identify the experiences constructed by people with venous ulcers, in the process of living with this chronic condition. This qualitative study was conducted between January and February 2013. A semi-structured interview was used, in which the participants were 14 people with venous ulcers treated at an outpatient angiology clinic of a municipality in the state of Rio Grande do Sul. The data were subjected to content analysis. The three categories submitted to analysis were: The venous ulcer and its impact on work; Changes in routine and limitations in living with the venous ulcer; and Living with the venous ulcer and the need for professional and family care. It was conclude that people with venous ulcers can present a propensity to develop problems that jeopardize their physical and emotional health and that require integral care from healthcare professionals.